Two new POM‐based compounds modified by lanthanide–Schiff base complexes with interesting NLO properties. Issue 11 (24th October 2018) - Luo, Xi-Ming; Cui, Chen-Hui; Cao, Jia-Peng; Lin, Qing-Fang; Xu, Yan
Abstract : Two POM‐based lanthanide–Schiff base complexes have been successfully isolated under hydrothermal conditions. Interestingly, they show excellent two‐photon responses, suggesting that they have potential applications in the NLO field. Abstract : Two POM‐based lanthanide derivatives, namely triaqua[2, 6‐diacetylpyridine bis(semicarbazone)‐κ 5 O, N, N ′, N ′′, O ′]terbium(III)‐μ‐oxido‐[tricosa‐μ2 ‐oxido‐dodecaoxido‐μ12 ‐phosphato‐dodecamolybdenum(VI)] pentahydrate (1 ), [Tb(C11 H15 N7 O2 )(H2 O)3 ][PMo12 O40 ]·5H2 O, and the dysprosium(III) analogue (2 ), have been isolated successfully by the reaction of Keggin–POM [PMo12 O40 ] 3− (abbreviated asPMo12 ), the Ln 3+ ion and the Schiff base 2, 6‐diacetylpyridine bis(semicarbazone) (DAPSC) ligand under hydrothermal conditions. [Ln(DAPSC)(H2 O)3 ][PMo12 O40 ]·5H2 O is aPMo12 ‐supported cluster featuring a lanthanide–Schiff base complex [denotedLn– L (Schiff base) ]. Single‐crystal X‐ray diffraction analysis reveals that the Ln III ion is in a distorted tricapped trigonal prismatic arrangement, coordinated by six O atoms and three N atoms. Two O atoms and three N atoms are provided by one DAPSC ligand, while the additional O atoms originate from aPMo12 cluster and three water molecules. Hydrogen‐bonding interactions between adjacent clusters form an interesting three‐dimensional supramolecular structure. The identities of1 and2 were characterized by IR spectroscopy, thermogravimetric analysis and powder X‐ray diffraction. Interestingly, both compounds possess excellent two‐photon absorption (TPA) responses to the third‐order nonlinear optics (NLO) (2264 GM for1 and 941 GM for2 ), suggesting that they have potential applications in the field of nonlinear optics (NLO). To our knowledge, 1 and2 are the first POM‐basedLn– L (Schiff base) complexes showing excellent two‐photon responses. Meanwhile, the electrochemical properties of both compounds were studied in detail.